Practice Patterns in the Management of Strabismus in Pakistan: Doi: 10.36351/pjo.v36i2.889 - Ahmed, Nasir; Shaheer, Muhammad; Zahoor, Sarmad; Hamza, Salman; Asim, Samran (Pakistan Journal of Ophthalmology, 2020)
Purpose: To study the current practice patterns of pediatric ophthalmologists in the management of strabismus in Punjab. Study Design: Questionnaire based Practice pattern survey. Place and Duration of Study: Teaching hospitals of Punjab from July 2018 to July 2019. Material and Methods: This study was conducted at ophthalmology departments of various teaching hospitals of Punjab. A questionnaire was designed to find out the current practice pattern for management of strabismus. Ophthalmologists who were members of Ophthalmological Society of Pakistan (OSP), having their expertise in strabismus surgery for more than 5years and practicing pediatric ophthalmology were selected. Discussion was also held regarding questionnaire and practices being performed after filling the proforma. This data was compiled, analyzed and was converted to a summary in points. Results: We contacted 90 ophthalmologists out of whom 76 responded to our Questionnaire. Complete Orthoptic Assessment was performed by only 46% (35) of the ophthalmologists. Prism cover test was used as a diagnostic tool by 70 (92%) ophthalmologists. Rest of the ophthalmologists used Synoptophore with it. Percentage of ophthalmologists performing cycloplegic refraction was very low. Only 5 (6.57%) surgeons used adjustable sutures. Only 46% of surgeons used to explain the complications of Anesthesia. More than 90% of surgeons explained the surgical procedures being done, its complications, post-operative care and need to use glasses or need for orthoptic exercises. All the surgeons kept follow up of the patients on 1st post-operative day. Conclusion: The current practices in strabismus need to be standardized and a consensus should be developed at a national level.